The variation rule of TBM tunneling parameters in deep composite strata and the recognition method of boreability grade - Wang, Haibin; Cui, Guogang; Shi, Zhen; Zhang, Ling; Gao, Chengdeng; Ding, Ziwei (Scientific reports, 2025)
To evaluate the energy efficiency of tunneling with an open full-section road header constructed in deep coal composite strata, this study relies on the development project of the 1# backdraft tunnel in the western area of a mine located in Binchang, Shaanxi Province. The analysis is based on machine-rock data collected by the Tunnel Boring Machine (TBM) while excavating through various composite strata, including muddy sandstone layers, muddy sandstone and coal composite strata, coal strata, medium-coarse sandstone layers, medium-coarse sandstone, and fine sandstone composite stratum, fine sandstone stratum. Descriptive statistics, correlation analysis, regression analysis, and other Mathematical and statistical methods are used to analyze the change rule of TBM tunneling parameters in different formations, and the optimized regulation range of tunneling parameters is proposed. At the same time, the propulsion factor, tunneling speed, and tunneling specific energy are introduced as the boreability evaluation indexes, and a quantitative identification method of formation boreability level is established to reasonably classify the difficulty level of tunneling in different formations. The results show that: (1) the change characteristics of five main tunneling parameters in different formations are obtained through data preprocessing, and the change trends of tunneling speed and penetration in different formations are consistent, while the change trends of cutter speed, thrust, and torque are opposite to that of penetration. (2) The main tunneling parameters in different formations are analyzed by numerical statistics, and it is found that all of them are normally distributed, and the 25% and 75% position of data distribution is taken to the values of 25% and 75% of the data distribution are given, and the reasonable regulation range of each parameter is given. (3) The two characteristic parameters of thrust factor and tunneling specific energy are introduced to analyze the tunneling energy efficiency of TBM tunneling in different strata, and the variation of the characteristic parameters in a single stratum is small, and the oscillatory nature of them in composite strata is significantly higher than that of a single stratum by a factor ranging from 1.29 to 3.64. (4) The identifying method of the tunneling grade of a strata has been established based on the indicators of the tunneling speed and the energy consumption of tunneling, and a characteristic parameter is proposed to identify the level of the tunneling performance. The identification method of grade is established based on the index of tunneling speed and energy consumption, and the fluctuation correction factor of characteristic parameter is proposed to quantitatively evaluate the degree of difficulty of tunneling in six kinds of strata. The stratum boreability grade identification method proposed in this paper can effectively classify the composite strata under deep and complex geological conditions, and provide important reference and guidance for the assessment and prediction of stratum boreability and optimization of tunneling parameter control in the smooth running section of TBM.